A plasmonic supramolecular nanohybrid as a contrast agent for site-selective computed tomography imaging of tumor - Bindra, Anivind Kaur (2022)
Design of organic–inorganic hybrids by anchoring of plasmonic materials such as gold nanoparticles (AuNPs) on self-assembled organic substrates is useful but challenging. Herein, in situ anchoring of plasmonic nanoparticles on the surface of a designed spherical assembly via Au-S bond formation is presented. First, a thiol tailed pyrene derivative (2) undergoes solvent dependent self-assembly, transforming into an organic spherical aggregate (2agg). The thiol (-SH) rich surface of the organic assembly allows cumulative anchoring of AuNPs on the surface to form an organic–inorganic hybrid (Au@2agg). Further coating of biocompatible polyethylene glycol (PEG) leads to the construction of the final multicomponent system (PEG-Au@2agg) exhibiting morphological and spectroscopic features. The potential of PEG-Au@2agg as a bioprobe and a contrast agent is investigated by X-ray computed tomography (CT) experiments in vivo. High X-ray attenuation of directly anchored AuNP clusters on the surface of this supramolecular nanohybrids enhances the X-ray CT contrast and allows tracing of site-selective accumulation in mouse 4T1 breast tumor. Thus, this approach of designing organic–inorganic nanohybrids paves the way for developing future intelligent multifunctional nanosystems capable of cancer detection and imaging.